PDGF Mediates Activation of c-Jun-N-Terminal Kinase, AP-1 and NF-kB in Human Glioblastoma T98G cells - Parra , Eduardo; Rojas, Victor; Maturana, Juan Carlos (Research Developments in Medicine and Medical Science Vol. 3, 2023)
Considerable circumstantial evidence has accumulated which strongly implicates platelet derived growth factor (PDGF) as an autocrine and/or paracrine agent in the development of numerous human tumor types. The evidence is most complete in the case of glioblastomas which nearly invariably over-express one or both PDGF chains and commonly express one or more receptor subtypes. Although PDGF is involved in numerous steps of several signal transduction pathways, we discovered that inhibiting Jun kinase N-terminal kinase (JNK) stimulates gliomas in an autocrine manner. We looked into the role of PDGF in the regulation of human T98G glioblastoma cells grown in the presence and absence of a small interfering RNA (siRNA) targeting Jun-N-Terminal Kinase one (JNK1). T98G cells multiplied significantly faster with PDGF alone than untreated cells. Cells treated with siRNA against JNK-1, on the other hand, reduced growth rate and DNA synthesis, whereas cells treated with a combination of PDGF and siRNA had no effect on growth rate, DNA synthesis, or cell proliferation when compared to cells treated with either PDGF or siRNA against JNK1 alone. The siRNA-mediated inhibition of JNK-1 expression results in a weak reduction in the transcriptional activity of the activator protein-1 (AP-1) in the presence of PDGF and a marginal inhibition of NF-kB activity. The decline was more pronounced in the presence of PMA, a positive control that typically raises JNK-1 kinase activity. As a result, our findings imply that siRNA directed against c-Jun N terminal kinase 1 may play a significant role in controlling PDGF production and activity in glioblastoma cells.